A Comprehensive Analysis of Epilepsy in Kashmir: Application of the ILAE 2017 - Raina, Adnan Firdous; Nazir, Muzaffer; Kawoosa, Atif; Hilal, Sheikh; Baba, Tanveer; Paul, Shabeer; Sanie , Bashir (Nepal Journal of Neuroscience, 2001)
Introduction: Recently, the International League Against Epilepsy (ILAE) has proposed new classification schemes for seizures and epilepsy. The applicability of these classification schemes has not been studied in resource-poor countries. Our aim was to  find the relative frequency of different types of epilepsies in Kashmiri population presenting to the Department of Neurology, Superspeciality hospital.Materials and Methods: The data collected during the first visit included clinical details including details of seizure semiology. All patients  had EEG and MRI BRAIN. All these data were used to classify seizure type and epilepsy using ILAE classification schemes. The ILAE 2017 epilepsy definition was used to diagnose epilepsy. The average annual incidence rates (AAIR) and 95% confidence intervals (CI) were calculated for epilepsies by onset and by etiology.Results: The present study was done on 500 patients with a mean age of 34.1±12.89 years. Majority of patients i.e. 151 (30.2%) were